The Dialogue of the Messengers with the Community of the Town (Rhetorical and analytical study of Qur‘ānic verses from Sūrah Yāsīn) - Khan, Habib Ullah (Journal of Islamic and Religious Studies, 2016)
This article encompasses specifically the five verses of Sūrah Yāsīn with respect to rhetorical point of view. I tried my best to dig out mysteries of these verses rhetorically in addition to the sum of knowledge in the rhetorical Qur‘ānic studies. I have discussed the semantic aspects and elaborated these verses in the light of Qur‘ānic eloquence and also compared these verses with the verses of Sūrah Qa╖a╖ to derive the arguments of Qur‘ān 's miracles in the shades of rhetoric and eloquence. At the end of this article I concluded the exegesis of these verses with the best scientific consequences.